Histoire de la notation : du Moyen Age à la Renaissance - Colette, Marie-Noëlle; Popin, Marielle; Vendrix, Philippe (Paris Minerve, 2003)
Strangely enough, the history of musical notation remains a relatively unexplored field. Admittedly, detailed studies abound, numerous critical editions raise new questions, a few authors have even launched into the writing of manuals, while others have projected new concepts into the world of musicology, such as the crucial concept of orality.From the discoverers of the eighteenth and nineteenth centuries to the specialists of the late twentieth century, we have come a long way in understanding musical notation, and in particular the notations of the Middle Ages and the Renaissance. It seems impossible for musicologists today to grasp the entirety of this field of study: the amount of knowledge to be acquired often exceeds individual horizons.This book is an attempt to make up for this shortcoming. However, it does not claim to be exhaustive. Nor does it claim to offer a range of methods for transcribing ancient notations into modern notation. Its aim is simply to explore almost eight centuries of the history of notation in order to illustrate what is at stake, to provide keys to understanding systems that are as diverse as they are stimulating, and to measure as accurately as possible the place that the act of notation has occupied during these centuries of musical practice. (Translated with Deepl.com)
Keywords: Music history; Notation